2020
DOI: 10.1038/s41598-020-71619-1
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-like dielectric and magnetic properties of sub 100 nm thick single crystal Cr2O3 films on an epitaxial oxide electrode

Abstract: The manipulation of antiferromagnetic order in magnetoelectric Cr2O3 using electric field has been of great interest due to its potential in low-power electronics. The substantial leakage and low dielectric breakdown observed in twinned Cr2O3 thin films, however, hinders its development in energy efficient spintronics. To compensate, large film thicknesses (250 nm or greater) have been employed at the expense of device scalability. Recently, epitaxial V2O3 thin film electrodes have been used to eliminate twin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…It appears that growing the samples at 500 °C even with an additional post-annealing at 700 °C (sample #5, Table 1) is insufficient to realize an antiferromagnetic film responding to the field cooling procedure (green curve in Figure 2a). This finding is in line with the recent work by Vu et al, [43] where it is reported that a good crystallinity is observed for Cr 2 O 3 thin films grown at 700 °C (compare to the properties of thin films prepared at a lower temperature [44,45] ). While the sample grown at 800 °C (sample #3, Table 1) reveals the strongest change of the transversal resistance (red curve in Figure 2a), the film prepared at 900 °C (sample #4, Table 1, blue curve in Figure 2a) shows the weakest measured transverse resistance change among all samples.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It appears that growing the samples at 500 °C even with an additional post-annealing at 700 °C (sample #5, Table 1) is insufficient to realize an antiferromagnetic film responding to the field cooling procedure (green curve in Figure 2a). This finding is in line with the recent work by Vu et al, [43] where it is reported that a good crystallinity is observed for Cr 2 O 3 thin films grown at 700 °C (compare to the properties of thin films prepared at a lower temperature [44,45] ). While the sample grown at 800 °C (sample #3, Table 1) reveals the strongest change of the transversal resistance (red curve in Figure 2a), the film prepared at 900 °C (sample #4, Table 1, blue curve in Figure 2a) shows the weakest measured transverse resistance change among all samples.…”
Section: Resultssupporting
confidence: 92%
“…[44,45] Good crystallinity of Cr 2 O 3 thin films is observed when they are grown at 700 °C. [43] Furthermore, post-annealing of the room temperature grown Cr 2 O 3 thin films shows an increase in the size of individual grains. [56] Transmission Electron Microscopy Studies: TEM analysis was conducted on thin cross-sections of specimens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear magnetoelectric switching is defined by a critical energy product of electric field and magnetic field [10], meaning magnetoelectric switching of Cr2O3 requires either substantial static magnetic fields [106,107] or extraordinarily large voltages. This presents a significant engineering challenge for scaling of devices, as a Cr2O3 thin film must be able to withstand voltages large enough for switching, and significant work is currently focused on increasing the breakdown voltage or decreasing the switching threshold for thin films [108,109]. Thus far, magnetoelectric switching in thin film heterostructures has required substantial magnetic fields on the order of ~0.6-1 T [93,106,107], but the technology remains promising for scale multiferroic devices.…”
Section: Electric Field Control Of Exchange Biasmentioning
confidence: 99%
“…On the other hand, Cr 2 O 3 has particular photo-response properties, ensuring a good detection within a long and large optical range [11,12]. Numerous synthetic routes have been developed to obtain Cr 2 O 3 nanoparticles, such as hydrothermal, sol-gel, forced hydrolysis, radiation, sonochemical and hydrolysis-condensation processes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%